A NOVEL VALIDATED METHOD FOR EXTRACTION AND ESTIMATION OF DIMETHYL FUMARATE FROM VARIOUS TEXTILE MATRICES ON GC/MS. - Khan, Uzman; Bashir, Rashida; Naveed, Sabiha; Shakoor, Abdul; Batool, Madiha; Raza Bokhari, Syed Ahmad (International Journal of NeuroOncology and Therapeutics, 2025)
A novel and rapid analytical method was developed for the determination of extractable dimethyl fumarate (DMFu) in various materials, including leather, polyurethane (PU) leather, textiles, rubber, and silica gel pellets, using gas chromatography-mass spectrometry (GC/MS). DMFu was extracted using ethyl acetate and analyzed on a DB-624 capillary column with helium gas (99.9% purity) as the mobile phase. One target ion and two qualifier ions were selected for the identification and quantification of DMFu. Key pre-treatment parameters, such as extraction method, solvent, and time, were optimized to achieve optimal performance. Under the optimized conditions, the method demonstrated a recovery rate of 91% to 98% for the standard. The calibration curve exhibited excellent linearity with a regression value of 0.9995 and a working range of 0.01–0.50 mg L⁻¹. The relative standard deviation (RSD) was ≤10% for test specimens and ≤5% for the pure standard. The method's limit of detection (LOD) and limit of quantification (LOQ) were 5×10⁻⁴ mg L⁻¹ and 5×10⁻³ mg L⁻¹, respectively. The developed method was successfully applied to real samples, revealing DMFu concentrations ranging from 1.34 mg L⁻¹ to 5.12 mg L⁻¹. This approach provides a reliable and efficient means for the accurate determination of DMFu in diverse materials.